Assessing the Pathogenic Ability of Ralstonia pseudosolanacearum (Ralstonia solanacearum Phylotype I) from Ornamental Rosa spp. Plants - Tjou-Tam-Sin, Napoleon N. A.; van de Bilt, Jeroen L. J.; Westenberg, Marcel; Gorkink-Smits, Peggy P. M. A.; Landman, N. Marco; Bergsma-Vlami, Maria (Frontiers in Plant Science, 2017)
Ralstonia pseudosolanacearum (Ralstonia solanacearum phylotype I) isolates found in stunted, yellowing and wilted ornamental rose (Rosa spp.) were assessed for their pathogenic ability in two rose cultivars (cv. ‘Armando’ and cv. ‘Red Naomi’) and in four solanaceous crops: tomato (Solanum lycopersicum cv. ‘Money maker’), tobacco (Nicotiana tabacum cv. ‘White Burley’), eggplant (Solanum melongena cv. ‘Black Beauty’) and sweet pepper (Capsicum annum cv. ‘Yolo Wonder’). Significant differences were observed in susceptibility between the two rose cultivars as well as between the two modes of inoculation performed. The cultivar ‘Armando’ was significantly more susceptible than cultivar ‘Red Naomi’, exhibiting higher disease severity and incidence. Similarly, stem inoculation after wounding was found to be significantly more effective than soil drenching, resulting in higher disease severity. . Additionally, a temperature dependency in susceptibility was observed for both cultivars irrespective of the mode of inoculation, however, this was significantly more pronounced upon soil drenching. The solanaceous crops all showed to be susceptible to the R. pseudosolanacearum isolates originated from the Rosa spp. plants. Furthermore, both rose cultivars were able to harbor symptomless infections with other R. pseudosolanacearum and R. solanacearum isolates than those isolated from rose. Our results clearly demonstrated that latent infections in a rose cultivar such as cv. ‘Red Naomi’ do occur even at temperatures as low as 20°C. This latency poses high risks for the entire floricultural industry as latently infected Rosa spp. plants are propagated and distributed over various continents, including areas where climatic conditions are optimal for the pathogen.